Prognostic Value of Androgen Receptor Splice Variant 7 in the Treatment of Metastatic Castration-Resistant Prostate Cancer: A Systematic Review and Meta-Analysis - Wang, Jiaxin; Zhang, Yucong; Wei, Chao; Gao, Xintao; Yuan, Penghui; Gan, Jiahua; Li, Rui; Liu, Zhuo; Wang, Tao; Wang, Shaogang; Liu, Jihong; Liu, Xiaming (Frontiers in Oncology, 2020)
Background The prognostic value of androgen receptor splice variant 7 (AR-V7) for the treatment response of metastatic castration-resistant prostate cancer (mCRPC) remains unclear. In this study, we aimed to synthesize relevant studies that assessed the prognostic value of AR-V7 status for the treatment response of mCRPC patients treated with androgen receptor signalling inhibitors (ARSis) and chemotherapy. Methods We searched the PubMed, Embase, and MEDLINE databases by using the keywords AR-V7 and prostate cancer to identify relevant studies published before 25 September 2019. The main outcomes were prostate-specific antigen (PSA) response, progression-free survival (PFS), and overall survival (OS). Pooled odds ratios (ORs) and hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated using a random effects model. The quality of the included studies was assessed using the Newcastle-Ottawa Quality Assessment Scale. Results A total of 1,545 patients from 21 studies were included. For the mCRPC patients treated with ARSis, AR-V7-positive patients had a lower PSA response rate (OR 6.01, 95% CI 2.88–12.51; P < 0.001), shorter PFS (HR 2.56, 95% CI 1.80–3.64; P < 0.001) and shorter OS (HR 4.28, 95% CI 2.92–6.27; P < 0.001) than AR-V7-negative patients. Although AR-V7-positive patients treated with chemotherapy also had a lower PSA response rate (OR 2.23, 95% CI 1.38–3.62; P = 0.001) and shorter OS than AR-V7-negative patients (HR 1.60, 95% CI 1.02–2.53; P = 0.043), there was no significant difference in PFS (HR 1.05, 95% CI 0.74–1.49; P = 0.796) between these groups. Furthermore, AR-V7-positive patients receiving ARSis had a shorter median OS than those receiving chemotherapy (HR 3.50, 95% CI 1.98–6.20; P < 0.001); There was no significant difference among AR-V7-negative patients (HR 1.30, 95% CI 0.64–2.62; P = 0.47). Conclusions AR-V7 is a potential biomarker of treatment resistance in mCRPC patients. AR-V7-positive mCRPC patients had poorer treatment outcomes than AR-V7-nagetive patients when treated with ARSis. AR-V7-positive patients have better outcomes when treated with taxane than ARSis. Furthermore, the ability of AR-V7 status to predict treatment outcomes varies from different detection methods. The detection of AR-V7 before treatment is important for the selection of treatment modalities for mCRPC patients.